2016
DOI: 10.1177/1687814016643454
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue properties of 6061-T6 aluminum alloy butt joints processed by vacuum brazing and tungsten inert gas welding

Abstract: Tungsten inert gas welding and vacuum brazing butt joints of Al-Mg-Si alloy 6061 in the artificially aged condition T6 were studied. Constant amplitude and variable amplitude fatigue loading tests were performed. The experimental S-N curves were compared with the fatigue design curves recommended by the International Institute of Welding, British Standard, and Eurocode 9. Two mean stress correction methods, Goodman and Gerber, were evaluated. In terms of the size effect on the fatigue life, this article propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…AWS D1.2 specifies a strength reduction of 40% associated with the HAZ formed during metal inert gas (MIG) welding of 6061, or a minimum retained strength of 165 MPa [41]. In addition, published data indicate comparable strength levels in tungsten inert gas (TIG) welded 6061, 169 -174 MPa [42].Thus, the results indicate AFSD provides some improvement in strength relative to 'acceptable' strength levels associated with relevant fusion processes, such as MIG and TIG welding.…”
Section: Discussionmentioning
confidence: 99%
“…AWS D1.2 specifies a strength reduction of 40% associated with the HAZ formed during metal inert gas (MIG) welding of 6061, or a minimum retained strength of 165 MPa [41]. In addition, published data indicate comparable strength levels in tungsten inert gas (TIG) welded 6061, 169 -174 MPa [42].Thus, the results indicate AFSD provides some improvement in strength relative to 'acceptable' strength levels associated with relevant fusion processes, such as MIG and TIG welding.…”
Section: Discussionmentioning
confidence: 99%
“…During microstructural analysis, it was observed that the grain re nement has taken place in the order of SZ < TMAZ < HAZ < BM, with average grain size of 4.77 µm in the SZ, 9.6 µm in the TMAZ, 56.73 µm in the HAZ, and 83 µm in the BM. Since the AA6061 is a heat treatable alloy, the precipitations of Mg 2 Si in Al 6061 are responsible to enhance the strength of the alloy [40]. Several investigations have demonstrated that the hardness of the aluminum alloys was mostly affected by precipitate distribution rather than grain size [41].…”
Section: Micro-hardnessmentioning
confidence: 99%
“…Although it has a perfect melting temperature, its wettability is much worse than that of Al-Si alloy, and more importantly, the corrosion resistance of Al-Zn alloy is much lower than that of Al-Si alloy, which makes it difficult to be used in heat exchangers [ 17 , 18 ]. Mg can break oxide film on the surface of aluminum alloys in vacuum conditions since Mg has stronger atomic activity and higher vapor pressure than Al, making Al-Mg alloy often used as a vacuum brazing filler metal [ 19 , 20 , 21 ]. However, due to the low production efficiency of vacuum brazing technology and the pollution of Mg steam to equipment, its application is not as wide as that of NOCOLOK flux brazing technology.…”
Section: Introductionmentioning
confidence: 99%